From P‐Functional Thiazol‐2‐thione Derivatives to Phosphaalkenes. Issue 11 (18th March 2019) - Begum, Imtiaz; Schnakenburg, Gregor; Han, Zeyu; Franconetti, Antonio; Frontera, Antonio; Gates, Derek P.; Streubel, Rainer
Abstract : A facile synthetic methodology is reported that permits access to the backbone (Et2 N)2 P‐substituted thiazol‐2‐thione 2 [(Et2 N)2 P‐THS Me ; THS Me = 3‐methylthiazol‐2‐thione‐5‐yl]. Starting from 2, Et2 N(Cl)P‐substituted thiazol‐2‐thione 3 [Et2 N(Cl)P‐THS Me ] was formed using chloride scrambling with PCl3 . Subsequently, nucleophilic substitution using Ph2 CHLi afforded [Et2 N(Ph2 CH)P‐THS Me ] (4 ) which, via reaction with PCl3, afforded [Ph2 CHP(Cl)THS Me ] (5 ). Conversion of 4 into phosphaalkene [Ph2 C=P‐THS Me ] (6 ) was achieved, but its thermal instability precluded isolation. Complex [κ P ‐W(CO)5 {Ph2 CH(Cl)P}‐THS Me ] (7 ) was then synthesized and used to access end ‐on complex [W(CO)5 (Ph2 C=P‐THS Me )] (8 ); the 1, 2‐addition product of 8 with H2 O, complex [Ph2 CH(OH)P‐THS Me ] (10 ), was confirmed by X‐ray crystallography. The head‐to‐tail dimers of 8, the diastereomeric dinuclear 1, 3‐diphosphetane complex 9 were assigned based on NMR results. In contrast, DFT calculations of all regio‐ and stereochemical isomers of 9 revealed a slight energetic preference for the head‐to‐head dimer. However, since transition states could not be localized, a detailed computational rationale for these experimental findings remains open. Abstract : A C ‐phosphanylated thiazol‐2‐thione was converted into a suitable pre‐cursor for an unstable phosphaalkene. Astonishingly, also the end‐on phosphaalkene complex wasn't stable towards dimerization.